Guidelines for the Development of Marketing Mix to the Fruit Festival in Rayong Province - Ruang-iem, Gawinrat (Dusit Thani College Journal, 2020)
This research article aimed to study personal factors and Thai tourists’ behavior factors affecting marketing mixes of fruit festival in Rayong Province. It would provide the developmental guidelines of the marketing mixes to upgrade the fruit festival in Rayong Province. The researcher used questionnaires as the research instrument in collecting quantitative data with 405 Thai tourists, who travelled in the fruit festival to Rayong Province and interview scripts to collect qualitative data from community representatives and government agencies in the area of Taphong Subdistrict and Nhongtaphan Subdistrict, Rayong Province. Then, the obtained data was analyzed by Statistical Package for the Social Sciences (SPSS). The research found that 40.7% of tourists had the objectives to travel to buy inexpensive fruits, and they prioritized the product in the marketing mixes, particularly variety of fruits with the mean of 3.73 When analyzed by inferential statistics, it showed that personal factors and Thai tourists’ behavior factors affecting the marketing mixes at a significance level (of 0.05). For the interview with the community representatives and government agencies showed that there should be a development of setting the interesting festival and a persuasive presentation of the seasonal fruits. Therefore, the developmental guidelines of the important marketing mixes which the organizers have to develop each marketing mix should get along with the standard exhibition venue in order to upgrade the fruit festival establishment in Rayong Province.